(untitled) (Current Horticulture, 2024)
An experiment was conducted to evaluate acid lime (Citrus aurantifolia Swingle) clones for pickle making at Citrus Research Station, Tirupati, during 2021 and 2022 with two replications in a completely randomized design with fifteen acid lime clones. The mean performance of pickle recovery was 49.26%, highest in TAL 94/14 (56.00%) and least in Phule Sharbati (42.00%). There was good texture (8.20), taste (8.50) and overall acceptability (8.40) in TAL94/14, whereas, best colour (8.20) and flavour (8.30) were observed in Local Kagzi lime and Balaji clones. The total bacterial population (CFU/g) was counted for four months period from the 0th day to 120th day at monthly interval. The least bacterial count was observed in clone TAL 94/14 on the 0th, 30th and 90th day. However, Balaji recorded least bacterial population on 60th and 120th day.